A study on diesel engine performance using biodiesel from waste cooking oil (WCO) - Nur Atiqah , Ramlan (2015)
The energy consumption, especially in the transport sector, has increased tremendously over decades. The extensive usage has led to an increased demand for petroleum, such as gasoline and diesel fuel, hence causing the depletion of fuel stocks. As concerns mount for long-term energy conservation, it becomes necessary to develop alternative fuels that have properties comparable with diesel fuel. Biodiesel from waste cooking oil (WCO) should be highlighted as a potentially economical alternative fuel. Therefore, the objective of this research is to investigate the engine performance as well as exhaust emission of biodiesel blends produced from WCO by using a single cylinder diesel engine (YANMAR TF 120). There were three types of biodiesel blends used throughout this study, namely the B5 WCO, which is 5% WCO biodiesel with 95% diesel, the B20 WCO with 20% WCO biodiesel with 80% diesel and the B100 WCO, with 100% WCO biodiesel without any diesel added. The results produced by biodiesel blends were compared with that of the diesel fuel. The parameters that were measured during the engine testing included in-cylinder pressure, power, torque, and exhaust emissions. From the in-cylinder pressure, calculations were made to obtain the rate of heat release. Results showed that among all the fuels tested, B5 WCO showed the closest trend to diesel. All fuels gave the highest peak pressure at 1500 rpm and B100 WCO marked the highest point compared to other fuels tested. Moreover, for power and torque performance, all test fuels presented the same trend, with diesel dominated the highest value for both results. In terms of rate of heat release, all biodiesel blends also showed similar trends as diesel. For gas emissions, biodiesel blends, especially the B100 WCO showed some improvement in the reduction of NOR, NO, CO, CO 2 and PM. Finally, it can be concluded that the engine performance and exhaust emissions of all biodiesel blends were compatible and can be operated using diesel engine at certain speeds. The results obviously showed that engine performance using 135 WCO was slightly similar to diesel fuel. Therefore, B5 WCO can be used as a diesel substitute.